Strategies for efficient production of recombinant proteins in Escherichia coli: alleviating the host burden and enhancing protein activity - Zhang, Zi-Xu; Nong, Fang-Tong; Wang, Yu-Zhou; Yan, Chun-Xiao; Gu, Yang; Song, Ping; Sun, Xiao-Man (Microbial cell factories, 2022)
Escherichia coli , one of the most efficient expression hosts for recombinant proteins (RPs), is widely used in chemical, medical, food and other industries. However, conventional expression strains are unable to effectively express proteins with complex structures or toxicity. The key to solving this problem is to alleviate the host burden associated with protein overproduction and to enhance the ability to accurately fold and modify RPs at high expression levels. Here, we summarize the recently developed optimization strategies for the high-level production of RPs from the two aspects of host burden and protein activity. The aim is to maximize the ability of researchers to quickly select an appropriate optimization strategy for improving the production of RPs.